Pendeteksian Kendaraan dengan Menggunakan Metode Running Average Background Substraction dan Morfologi Citra - Rifki Kosasih; Muhammad Arfiansyah (STMIK Budi Darma, 2020)
Traffic conditions on the highway at this time has started to be crowded. To find out if there is traffic jam or can not be seen by counting the number of vehicles passing through the area. However, it is impossible for security forces to count the number of vehicles manually. This requires a method that can be used and is calculated from the number of vehicles. In this study, the running average background substraction method and morphological operations were used to detect vehicles and use the center of the object (centroid) to calculate the number of vehicles. The sample used is a traffic video in the Bekasi area. From the research results, there were 37 vehicles detected in real conditions and stated as vehicles in the application and there were 7 vehicles detected in real conditions but not stated in the application. The next stage is an evaluation by calculating the value of precision, recall and accuracy. In this study, the precision value obtained was 84.09%, the recall value was 94.87% and the accuracy rate was 80.43%.